2019
DOI: 10.1002/celc.201900129
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium Phosphide: A New Type of Hydrogen Oxidation Reaction Catalyst with Non‐Linear Correlated Catalytic Response to pH

Abstract: Rh 2 P nanoparticles were colloidally synthesized and used as electrocatalysts toward the hydrogen oxidation reaction (HOR) in alkaline electrolyte for the first time. It was found that Rh 2 P exhibits remarkable catalytic performance, which is superior to Rh and even commercial Pt/C and can be attributed to the synergistic effect caused by the P atoms on the surface of Rh 2 P. This work might open up a new avenue for expanding the family of electrocatalysts with advanced HOR performance in alkaline electrolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 38 publications
1
18
0
1
Order By: Relevance
“…[ 123 ] Chen's group investigated Rh 2 P NPs as a new type of Pt‐free HOR catalysts ( Figure a,b), with normalized exchange current densities of 0.65 mA cm −2 and 0.52 mA µg −1 , respectively, about 2.4 and 1.4 times higher than its Rh counterpart, even superior to Pt/C (Figure 5c). [ 124 ] Compared to the alkaline fuel cell, the proton exchange membrane (PEM) fuel cell possesses certain advantages such as employing commercialized PEM (Nafion film) and air as the oxidant, which appeals to more practical applications. [ 125 ] Kucernak et al demonstrated that palladium phosphides (PdP 2 , and Pd 5 P 2 ) possessed excellent HOR activity in 0.1 m HClO 4 electrolytes (Figure 5d).…”
Section: Applications In Energy‐related Electrocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…[ 123 ] Chen's group investigated Rh 2 P NPs as a new type of Pt‐free HOR catalysts ( Figure a,b), with normalized exchange current densities of 0.65 mA cm −2 and 0.52 mA µg −1 , respectively, about 2.4 and 1.4 times higher than its Rh counterpart, even superior to Pt/C (Figure 5c). [ 124 ] Compared to the alkaline fuel cell, the proton exchange membrane (PEM) fuel cell possesses certain advantages such as employing commercialized PEM (Nafion film) and air as the oxidant, which appeals to more practical applications. [ 125 ] Kucernak et al demonstrated that palladium phosphides (PdP 2 , and Pd 5 P 2 ) possessed excellent HOR activity in 0.1 m HClO 4 electrolytes (Figure 5d).…”
Section: Applications In Energy‐related Electrocatalysismentioning
confidence: 99%
“…Reproduced with permission. [ 124 ] Copyright 2019, Wiley‐VCH. d) Hydrogen oxidation in a H 2 saturated solution, Inset: HOR response normalized to limiting HOR current density.…”
Section: Applications In Energy‐related Electrocatalysismentioning
confidence: 99%
“…DFT results reveal that the introduction of P into Rh can weaken the ∆GHad of Rh2P to nearly zero. The HOR specific and mass activities of Rh2P nanoparticles are 0.65 mA•cm −2 and 0.52 mA•μg −1 , which is 2.4 and 1.4 times higher than those of Rh/C (0.27 mA•cm −2 and 0.37 mA•μg −1 ), and even surpass the activity of Pt/C in alkaline media 125 . However, considering the element abundance and price of Rh, it is not a good choice as a HOR catalyst than other inexpensive materials.…”
Section: Other Metal Based Catalystsmentioning
confidence: 82%
“…While cobalt phosphide 7,17,18,21,22 and rhodium phosphide [23][24][25][26][27][28][29] catalysts have both been the subject of active study in recent literature, the catalytic properties [30][31][32][33] of iridium phosphides have been less explored outside of structural and physical studies over the last half century, [34][35][36][37][38][39][40][41][42][43][44][45] in part due to their difficult syntheses. 46 This is in spite of the fact that, given the similarity often observed in the behavior of metal phosphides to their metal analogues, iridium-derived catalysts have often been found to be exceptional catalysts for reactions of great industrial value 47, 48 such as alkane dehydrogenation.…”
Section: -20mentioning
confidence: 99%